Intrinsic retinoic acid synthesis is required for oligodendrocyte progenitor expansion during CNS remyelination - Nanescu, Sonia E.; Wathieu, Natacha M.; Rosko, Lauren; Cha, David S.; Kumar, Mahesh N.; Olszewski, Rafal T.; Reger, Joan; Baydyuk, Maryna; Dua, Alisha N.; Krezel, Wojciech; Zujovic, Violetta; Huang, Jeffrey K. (Frontiers in Cellular Neuroscience, 2025)
Myelin regeneration (remyelination) in the CNS depends on the recruitment, proliferation and differentiation of oligodendrocyte precursor cells (OPCs) at demyelinated lesions. However, despite the presence of OPCs, very few oligodendrocytes and myelin are regenerated in chronic multiple sclerosis (MS) lesions for reasons that remain poorly understood. Here, using a spontaneous remyelination model in mice, we found that retinaldehyde dehydrogenase 2 (Raldh2), a rate-limiting enzyme for retinoic acid (RA) synthesis, is upregulated in OPCs and in a subpopulation of microglia/macrophages during remyelination. Tamoxifen induced deletion of Raldh2 globally, or conditionally in OPCs, resulted in significantly fewer proliferating OPCs in lesions, leading to decreased oligodendrocyte numbers and myelin density. Moreover, induced deletion of Raldh2 globally also resulted in increased microglia/macrophage density in lesions. Further, exogenous RA delivery into lesions significantly increased oligodendrocyte lineage cells, while also decreasing proinflammatory microglia/macrophages, with no significant effect on anti-inflammatory microglia/macrophages. Postmortem MS brain sections revealed Raldh2 was absent in the majority of OPCs in chronic inactive lesions compared to the other lesion types. These results suggest that Raldh2 upregulation in lesions is critical for OPC proliferation during remyelination, and reveal that the failure to regenerate sufficient oligodendrocytes and myelin in chronic MS lesions may arise from impaired OPC expansion due to the failure to intrinsically synthesize RA.